Authoring the Self - Hess, Scott (Literary Criticism and Cultural Theory, 2005)
Drawing upon historicist and cultural studies approaches to literature, this book argues that the Romantic construction of the self emerged out of the growth of commercial print culture and the expansion and fragmentation of the reading public beginning in eighteenth-century Britain. Arguing for continuity between eighteenth-century literature and the rise of Romanticism, this groundbreaking book traces the influence of new print market conditions on the development of the Romantic poetic self.